Hierarchy of the Russian Church and Relations between the Horde and the Russian Church during the Tatar-Mongol Invasion of 1237–1240 according to Contemporary Estimates. - T.R. Galimov (Золотоордынское обозрение)
Objective: The author analyzes activities of the Russian church and its supreme hierarchs during the most active period of the Russian-Horde conflict (1237–1240). Materials: Old Russian chronicles and tales remain the main source of information on the activities of the church hierarchy during the military-political confrontation between Russian principalities and the Horde. As it has been shown by studies of recent years, complex of scenes depicting the struggle against the invaders is not so clear, as it was considered to be in the national historiography for many decades. This observation allows a new reading of the reports on church life in Rus’ during the most acute phase of Russian-Horde war. Results and novelty of the research: Events of 1237–1240 led to a fundamental change in the existing situation in Rus’. This concerned not only the power but also religious institutions. The results of this study suggest that behavior of church hierarchs became the main cause of changes in the socio-political and economic spheres of ancient Russian ecclesiastical organization. The church accepted the rule of the Horde over Rus’ and the Horde benefits and awards reinforced the higher clergy’s loyalty to the khans’ power. This circumstance required the church to declare its stance in respect to the new power. As a result, the need for accepting existing relations between the church and the Horde found its justification in the concept of “Plagues of God”. Such an ideological justification removed conquerors’ responsibility for the ills that befell Rus’ and justified contacts between the church and the Horde. Old Russian sources do not provide direct estimates of the prelates’ behavior. But reading of the chronicle reports leave the impression that contemporaries assessed the behavior of the church quite ambiguously and probably reprehensibly.